Financial integration in Asia: new Empirical evidence using dynamic panel data estimations - Erkut, Burak; Sharma, Gagan Deep (Springer Heidelberg, 2023)
The aim of this work is to examine financial integration in Asia between 1970 and 2018 by using dynamic panel data methods, covering first and second generation panel unit root tests, cointegration, common correlated effects models, dynamic ordinary least squares and fully modified ordinary least squares models, augmented mean group, and Arellano-Bond dynamic panel data estimations. This research utilizes data for 13 Asian economies between 1970 and 2018 based on the World Bank's World Development Indicators. The focus of the data analysis is on domestic saving and investment rates, operationalized as gross domestic saving and gross fixed capital formation. The results highlight that these rates are integrated at I(1); there is evidence of cointegration, and the causality between saving and investment for these Asian economies is statistically significant and bidirectional. Furthermore, we also estimate the coefficients of the long-run relationship by using panel data methods. Using the Dumitrescu-Hurlin causality analysis, we identify a bidirectional causality between investments and savings for Asia. Overall, our results deliver statistically significant empirical evidence with contemporary econometric methods to understand the degree of Asian financial integration.
Keywords: Asia; Financial integration; Feldstein-Horioka puzzle; Economic integration